Current Understanding of Host Genetics of Otitis Media - Geng, Ruishuang; Wang, Qingzhu; Chen, Eileen; Zheng, Qing Yin (Frontiers in Genetics, 2020)
The pathogenesis of otitis media, inflammation of the middle ear, involves the interplay of many different factors such as pathogenicity of infectious pathogens, host immunological status, genetic predisposition, and environmental factors. Genetics have been known to be key determinants of otitis media (OM) susceptibility. Studies from animal models and human genetics have identified many genes and variants associated with susceptibility to otitis media. These include genes encoding components of multiple signaling pathways that are involved in host immunity; inflammatory responses of the middle ear mucosa, genes involved in cellular function, such as mucociliary transport, mucin production, and mucous cell metaplasia; and genes that are essential for middle ear cavitation and homeostasis and epithelial cell development. Since our last review, some new mouse models with mutations in genes like CCL3, IL-17A, and Nisch have been reported. Genetic variants and polymorphisms of several genes, such as FNDC1, FUT2, A2ML1, TGIF1, CD44, and IL1-RA VNTR allele 2, have been identified to be significantly associated with OM. This review is focused on the current understanding of host genetics of OM and recent discoveries. Continued studies on the identified genes and discovery of new genes employing advanced technologies, such as gene editing, next generation sequencing and genome-wide association study, will advance our understanding of the molecular mechanism underlying the pathogenesis of otitis media. This would open avenues for developing effective therapies.